2013
DOI: 10.1016/j.ijcard.2012.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the development of chagasic cardiomyopathy: Role of PI3Kinase/NO axis

Abstract: Altogether our results demonstrate that heart failure in Chagas' disease may occur due to electrical and mechanical remodeling of cardiac myocytes, and suggest that AKT/PI3K/NO axis could be an important pharmacological target to improve the disease outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 36 publications
8
42
0
Order By: Relevance
“…9,22,23 In a previous study, we have shown that Colombian strain of T. cruzi causes marked collagen accumulation in the mice left ventricle. As shown in Figure 1A, using Picrosirius staining technique, we detected progressive collagen deposition in right ventricle of infected mice.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…9,22,23 In a previous study, we have shown that Colombian strain of T. cruzi causes marked collagen accumulation in the mice left ventricle. As shown in Figure 1A, using Picrosirius staining technique, we detected progressive collagen deposition in right ventricle of infected mice.…”
Section: Resultsmentioning
confidence: 94%
“…9 Thus, we used isolated right ventricular myocytes and patch-clamp technique to study the impact of Chagas disease on plasmatic membrane electrical properties.…”
Section: 3mentioning
confidence: 99%
See 3 more Smart Citations